Reading the Brussels Palimpsest in the History of the Nouveau Plan de Bruxelles Industriel (1910) - Declève, Marine (2020)
This article restores the dialogical link between the Nouveau Plan de Bruxelles Industriel avec ses Suburbains, published on the occasion of the 1910 Industrial Exhibition (Verwest, Vanderoost, & Xhardez, 1910a), and the Inventaire Visuel de L’architecture Industrielle de L’agglomération de Bruxelles, produced by Maurice Culot and the team at the Archives d’Architecture Moderne (AAM) between 1980–1982 (Culot & the AMM, 1980–1982). These two kinds of spatialised visual inventories of places dedicated to production brings out a layer of the Brussels palimpsest filled with information that goes beyond the categories of permanence, persistence and disappearance raised by André Corboz and Alain Leveillé’s cartographic implementation of the palimpsest theory in the Atlas du Territoire Genevois (Corboz, 1993). This article compares palimpsest theory as applied to Geneva to the practice of inventory in Brussels. We propose visualising a lisuel layer intended as a visual reading revealed through a process of description, extraction, classification and juxtaposition. This process of visual analysis helps construct a typology of manufacturing production whose traces are embedded in urban space. It shows how a cartographic document informs the 1910 urban project and how local manufacturing companies contributed to its implementation. The contribution of this cartographic investigation is threefold. It concerns forms of manufacturing companies, forms of living, and production of urban space in 1910 Brussels. The Brussels Industrial Exhibition and the spatial story of Louis De Waele’s public works company reveals two patterns of relationships between industrial production and the transformation of urban space.